Assessing Teacher Beliefs Regarding Research-Based Practices to Improve Services for GT Students. Issue 4 (October 2019) - Johnsen, Susan K.; Kaul, Corina R.
This study examined teacher beliefs regarding research-based practices in gifted education and how these beliefs or other barriers influenced the implementation of practices in their classroom. An online survey was sent to gifted education teachers in a large suburban district. The teacher belief statements were developed based on the National Association for Gifted Children (NAGC) Pre-K-Grade 12 Gifted Programming Standards . Although a majority of the teachers agreed with the research-based belief statements, fewer implemented the practice in their classrooms frequently. If they did implement the practice, they perceived positive student outcomes. Teachers did identify these obstacles related to implementation: limited resources, training, skill level, and the school system curriculum.